Survei Literasi Sains Peserta Didik Pada Dimensi Sikap Terhadap Sains - Rum, Muh.; Martawijaya , M. Agus; Khaeruddin , Khaeruddin; Hasyim, Mutahharah (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
This research is survey research. This study aims to determine the science literacy of students in terms of the dimension of attitudes towards science. This research was carried out in the odd semester of the 2021/2022 school year. The subjects in this study were students of class XII MIPA SMA Negeri 8 Maros. The instrument that used in this study was a attitudes questionnaire of scientific literacy. Data collection is carried out through the provision of questionnaires. The data from the research that was tested for validity were then analyzed quantitatively. The results of this study show a positive attitude towards Science, this is based on the results of research based on 4 indicators of attitudes towards Science, namely support for scientific investigations as much as 68.92%, student confidence in science by 69.86%, interest, motivation and involvement in science by 65%, and responsibility for resources and the environment by 72.06%. The results of the study based on these 4 indicators show that the attitudes of students tend to have a positive attitude towards science, in other words, students of SMA Negeri 8 Maros are enjoyed the science.